Prognostic significance of mast cell and microvascular densities in malignant peripheral nerve sheath tumor with and without neurofibromatosis type 1 - Roberto André Torres de Vasconcelos; Pedro Guimarães Coscarelli; Thyago Marsicano Vieira; Washington Silva Noguera; Davy Carlos Mendes Rapozo; Marcus André Acioly (Cancer Medicine)
Abstract Malignant peripheral nerve sheath tumors (MPNSTs) are rare and aggressive soft tissue sarcomas with a significant susceptibility to metastasize early in their course. Pathogenesis is yet to be fully elucidated. Recently, the essential role of mast cells in the tumor onset of neurofibromatosis type 1 (NF1)‐associated neurofibromas and MPNSTs was confirmed in both experimental and human studies. In this study, we investigate mast cell density (MCD), microvascular density (MVD), and proliferation index (Ki‐67) in MPNST. A secondary aim was to correlate histological staining to clinical data and survival in patients with and without NF1. In total, 34 formalin‐fixed paraffin‐embedded MPNST tissues from 29 patients were eligible. MCD, MVD, and Ki‐67 labeling index (LI) were analyzed in all stained tissues by a computer‐based quantitative algorithm (Aperio ImageScope). In addition, chart review was performed for clinical data and survival analysis. Overall, MCD, MVD, and Ki‐67 LI were evenly distributed throughout tumor tissue. There was a negative correlation of NF1 status (affected, P = 0.037), tumor size (>10 cm, P = 0.023), and MVD in the tumor periphery (higher tercile, P = 0.002) to survival. Multivariate analysis confirmed the association of MVD in the tumor periphery (higher tercile, P = 0.019) with a decreased overall survival. Diverse mast cell and microvascular distributions suggest that angiogenesis in MPNST occurs independently. The role of mast cells in tumor progression is unclear and lacks prognostic value. Higher MVD has prognostic significance with possible therapeutic implications in MPNST.